Importance of sustainable polymers for modern society and development - Md. Rezaur, Rahman; Nur-Azzah Afifah, Taib; Muhammad Khusairy, Bakri; Siti Noor Linda, Taib (Elsevier Ltd, 2021)
Polymers are one of the most important and enormously used materials in the modern society. Scientists and researchers keep on improving this material via their studies and research, in order to come up with sustainable properties with the finest products. In this study the significance of sustainable polymers for modern society and development had been expanded. In addition, the current applications of synthetic and biodegradable polymers and its positive and negative impacts on the environment are also stated. The polymeric materials waste management and the sustainability of biodegradable polymers are specified.